2013
DOI: 10.1186/1748-717x-8-133
|View full text |Cite
|
Sign up to set email alerts
|

The impact of flattening-filter-free beam technology on 3D conformal RT

Abstract: BackgroundThe removal of the flattening filter (FF) leads to non-uniform fluence distribution with a considerable increase in dose rate. It is possible to adapt FFF beams (flattening-filter-free) in 3D conformal radiation therapy (3D CRT) by using field in field techniques (FiF). The aim of this retrospective study is to clarify whether the quality of 3D CRT plans is influenced by the use of FFF beams.MethodThis study includes a total of 52 CT studies of RT locations that occur frequently in clinical practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…However, removal of the flattening filter has greatly increased the dose output by two to threefold and the time required to deliver the total MU was reduced, which had outweighed the time needed by the increased MU. This was in line with the several previous studies in which reduction of TT of 20–50% have been reported 17,20,21. Because of this advantage, the use of FFF beams has been extended to VMAT treatment of nasopharynx22 and prostate23 cancers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, removal of the flattening filter has greatly increased the dose output by two to threefold and the time required to deliver the total MU was reduced, which had outweighed the time needed by the increased MU. This was in line with the several previous studies in which reduction of TT of 20–50% have been reported 17,20,21. Because of this advantage, the use of FFF beams has been extended to VMAT treatment of nasopharynx22 and prostate23 cancers.…”
Section: Discussionsupporting
confidence: 88%
“…This was in line with the several previous studies in which reduction of TT of 20-50% have been reported. 17,20,21 Because of this advantage, the use of FFF beams has been extended to VMAT treatment of nasopharynx 22 and prostate 23 cancers. Nevertheless, despite the FFF beam technology demonstrated attractive practical advantages over the conventional beam IMRT, the understanding of the biological effect of such a high dose rate treatment on body tissues which may have consequence on late toxicities is still not certain and needs to be proven by longer term clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, flattening-filter-free (FFF) beams can be applied in both IMRT and VMAT treatment planning, with the practical advantage of much higher dose rates as compared with normal flat beams [6]. A draw-back to be considered here is that the conical beam profile of FFF beams is generally found to require more segments and/or more monitor units to achieve the same standards of PTV homogeneity than for flat beams (e.g., [7][8]); this again lengthens treatment time somewhat, particularly for large PTVs. The greatest reduction in treatment time may arise from a combination of arc treatment with FFF beams; however, here we will consider FFF beams in IMRT treatment planning because of its rapidly spreading availability.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Flatteningfilter-free (FFF) beams can increase delivery efficiency by employing a high-dose rate that greatly reduces the beam on time (BOT). [3][4][5][6][7][8] This makes them useful for treatments requiring a high dose per fraction, such as SBRT. The increased efficiency of FFF beams can also aid in respiratory motion management, including the use of voluntary breath hold techniques, by enabling entire beam delivery within a short number of breath holds.…”
Section: Introductionmentioning
confidence: 99%